2020
DOI: 10.1001/jamanetworkopen.2020.25594
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated With US Adults’ Likelihood of Accepting COVID-19 Vaccination

Abstract: IMPORTANCE The development of a coronavirus disease 2019 (COVID-19) vaccine has progressed at unprecedented speed. Widespread public uptake of the vaccine is crucial to stem the pandemic. OBJECTIVE To examine the factors associated with survey participants' self-reported likelihood of selecting and receiving a hypothetical COVID-19 vaccine. DESIGN, SETTING, AND PARTICIPANTS A survey study of a nonprobability convenience sample of 2000 recruited participants including a choice-based conjoint analysis was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

94
738
18
13

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 678 publications
(863 citation statements)
references
References 33 publications
94
738
18
13
Order By: Relevance
“…Vaccine attributes posed prevalent concerns, particularly due to the newness of COVID-19 vaccines [22,48]. The most commonly cited reasons for hesitation or refusal were fear of side effects [1,22,47,49,50], safety [5,34,37,51], and effectiveness [2,5,24,[52][53][54]. Belief that vaccines are unnecessary [43,50,52,55], inadequate information [34,47,50], unknown/short duration of immunity [2,5,50,53], and a general anti-vaccine stand [1,10,55] were associated with lower acceptance.…”
Section: Vaccine Attributes and Individual Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccine attributes posed prevalent concerns, particularly due to the newness of COVID-19 vaccines [22,48]. The most commonly cited reasons for hesitation or refusal were fear of side effects [1,22,47,49,50], safety [5,34,37,51], and effectiveness [2,5,24,[52][53][54]. Belief that vaccines are unnecessary [43,50,52,55], inadequate information [34,47,50], unknown/short duration of immunity [2,5,50,53], and a general anti-vaccine stand [1,10,55] were associated with lower acceptance.…”
Section: Vaccine Attributes and Individual Factorsmentioning
confidence: 99%
“…One survey reported that 17.1% would get the vaccine only if covered by insurance [54] and another found 49% expected it to be free (paid by insurance or government) [56]. In America, US-made vaccines were more trusted than China-made [53,57] or foreign-developed [5,53]. Most Chinese (64%) expressed no preference for domestic or foreign-made [34].…”
Section: Vaccine Attributes and Individual Factorsmentioning
confidence: 99%
“…A previous study found that 50% vaccine efficacy was associated with a 51% rate of acceptance. [38] The manufacturing country was another reason given for accepting the vaccine (in 28.6% of respondents). This finding is similar to results from a US survey related to hypothetical vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…The surveyed individuals had lower acceptance of the vaccine if it originated from a country outside the United States. [38] Other contributing factors, such as fewer adverse effects,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation